2021
DOI: 10.3389/fendo.2021.774567
|View full text |Cite
|
Sign up to set email alerts
|

Higher Triglyceride–Glucose Index Is Associated With Increased Likelihood of Kidney Stones

Abstract: AimsWe aimed to assess the association between triglyceride–glucose (TyG) index and kidney stones in US adults.MethodsData were obtained from the 2007–2014 National Health and Nutrition Examination Survey (NHANES). Participants aged ≥18 years who were not pregnant and provided complete data about TyG index and kidney stones were included in the analysis. Weighted multivariable regression analysis and subgroup analysis were preformed to estimate the independent relationship between TyG index and nephrolithiasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Likewise, insulin resistance may result in a reduction in renal ammonia production, which will lead to a reduction in ammonia buffering and further decrease urine pH ( 28 ). In urine with a pH below 5.5, less soluble uric acid is formed from urate, which can cause uric acid stones ( 29 ). Further, IR increases renal tubule citrate uptake and decreases urinary citrate levels ( 10 ), which is one of the primary causes of calcium stones.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, insulin resistance may result in a reduction in renal ammonia production, which will lead to a reduction in ammonia buffering and further decrease urine pH ( 28 ). In urine with a pH below 5.5, less soluble uric acid is formed from urate, which can cause uric acid stones ( 29 ). Further, IR increases renal tubule citrate uptake and decreases urinary citrate levels ( 10 ), which is one of the primary causes of calcium stones.…”
Section: Discussionmentioning
confidence: 99%
“…New research showed that the TyG index may be an important prognostic indicator of prediabetes patients and can independently predict new cardiovascular and cerebrovascular adverse events (35). Some studies have also proved that with the increase of TyG index, the risk of Diabetes also significantly increased and it was a risk markers of insulin resistance (36)(37)(38). BMI was known to be used to assess the risk of obesity and metabolic diseases and is the most readily available indicator calculated by height and weight (39).…”
Section: Comparisons With Other Studies and What Does The Current Wor...mentioning
confidence: 99%
“…Others had shown diverticular disease risk is positively associated with BMI, body fat percentage, and visceral fat area (Shih et al, 2022) (Freckelton et al, 2018) (Böhm, 2021). Similarly, kidney stones have been associated with the triglyceride-glucose (TyG) index (Qin et al, 2021), and atrial tachycardias have been associated with VLDL levels in metabolic syndrome patients (Lee et al, 2017) (Park & Lee, 2018). Our study is the first to suggest that these associations may be causally related and specific to plasma TG levels, as opposed to or in addition to confounding risk factors, such as obesity and hormone replacement therapy.…”
Section: Discussionmentioning
confidence: 99%